Growing girls : the natural origins of girls' organizations in America - Miller, Susan A., 1961- (Rutgers series in childhood studies., 2007)
In the early years of the twentieth century, Americans began to recognize adolescence as a developmental phase distinct from both childhood and adulthood. For boys, competitive sports as well as?primitive? outdoor activities offered by fledging organizations such as the Boy Scouts would enable them to combat the effeminacy of an overly civilized society. But for girls, the remedy wasn?t quite so clear. Surprisingly, the?girl problem??a crisis caused by the transition from a sheltered, family-centered Victorian childhood to modern adolescence where self-control and a strong democratic spirit.